The Nexus between Democracy and Income Inequality: Empirical Evidence from Some Selected African Countries - Lawal, Rahanatu; Ibrahim, Kekere S.; Abbah, Emmanual I. (Kashere Journal of Politics and International Relations, 2023)
In this paper, the study showed the relationship between democracy and income inequality, by first reviewing some theoretical and empirical issues that explained the complex dynamics between democracy and income inequality. While democracy is hypothesized to increase redistribution and to reduce inequality, and why this expectation may fail to be realized when democracy is captured by the richer segments of the population thus, exacerbating poverty and income inequality. Empirical evidence from this study is based on panel cointegration, causality, and OLS (a cointegrating regression model) (FMOLS). The result suggests the existence of cointegration between democracy and income inequality. The result also suggests a bidirectional causality running from democracy to income inequality and from income inequality to democracy. The FMOLS result shows that democracy is positively and significantly related to income inequality. The insights from this study are informative to policymakers in these African countries to strengthen their institution and reduce leakages, corruption, and elite control of power with little dividends of democracy to the people. This will go a long way to strengthen citizen support for a democratic regime.